Interactions Between Language and Mental Representations. Issue 3 (23rd June 2016) - Ünal, Ercenur; Papafragou, Anna
Abstract : It has long been recognized that language interacts with visual and spatial processes. However, the nature and extent of these interactions are widely debated. The goal of this article is to review empirical findings across several domains to understand whether language affects the way speakers conceptualize the world even when they are not speaking or understanding speech. A second goal of the present review is to shed light on the mechanisms through which effects of language are transmitted. Across domains, there is growing support for the idea that although language does not lead to long‐lasting changes in mental representations, it exerts powerful influences during momentary mental computations by either modulating attention or augmenting representational power.